The Role of GM-CSF Autoantibodies in Infection and Autoimmune Pulmonary Alveolar Proteinosis: A Concise Review - Ataya, Ali; Knight, Vijaya; Carey, Brenna C.; Lee, Elinor; Tarling, Elizabeth J.; Wang, Tisha (Frontiers in Immunology, 2021)
Autoantibodies to multiple cytokines have been identified and some, including antibodies against granulocyte-macrophage colony-stimulating factor (GM-CSF), have been associated with increased susceptibility to infection. High levels of GM-CSF autoantibodies that neutralize signaling cause autoimmune pulmonary alveolar proteinosis (aPAP), an ultrarare autoimmune disease characterized by accumulation of excess surfactant in the alveoli, leading to pulmonary insufficiency. Defective GM-CSF signaling leads to functional deficits in multiple cell types, including macrophages and neutrophils, with impaired phagocytosis and host immune responses against pulmonary and systemic infections. In this article, we review the role of GM-CSF in aPAP pathogenesis and pulmonary homeostasis along with the increased incidence of infections (particularly opportunistic infections). Therefore, recombinant human GM-CSF products may have potential for treatment of aPAP and possibly other infectious and pulmonary diseases due to its pleotropic immunomodulatory actions.